Prediksi Financial Distress Dengan Analisis Rasio Keuangan - Ni Nyoman Juli Nuryani (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
This study aims to determine the Effect of Liquidity Ratios, Profitability Ratios, Economic Profitability Ratios and Laverage Ratios on Financial Distress Predictions in the Banking Sector in the Indonesia Stock Exchange. This study uses a quantitative approach. The sample used is data on the banking sector that has gone public with a total of 10 banks in the 2016-2018 period. The analysis technique used in this study is the classic assumption test, multiple linear regression analysis of determination analysis and hypothesis testing with T-Test and F-Test. The results showed that the Liquidity Ratio, Provitability Ratio, Profitability Ratio and Leverage Ratio affect the Financial Distress Prediction of banking companies on the Indonesia Stock Exchange by 78.3% and the remaining 21.7% is influenced by other factors not examined in this study. Profitability ratio is the ratio that has the most dominant influence on the company’s Financial Distress Prediction.